Michael E. answered • 10/05/18

Specializing in the Math Portion of the GED

Hello James,

For the equation

f = c * [(1 + r)^{n} - 1] / r, multiply both sides by r,

→ fr = c * [(1 + r)^{n} - 1]. Divide both side by c

→ fr / c = (1 + r)^{n} - 1. Add 1 to both sides

→ fr / c + 1 = (1 + r)^{n}. Take the n'th root of both sides

→ ^{n}√[fr / c + 1] = ^{n}√[(1 + r)^{n}]. This will clear the radical on the right side, leaving just what is inside

→ ^{n}√[fr / c + 1] = 1 + r. Subtract 1 from both side, and you have 'r' alone

→ r = ^{n}√[fr / c + 1] - 1.

Thank you for the question. If you message me directly, I can provide a better formatted version.

Kind regards,

Michael E.

Michael E.

10/09/18

James W.

I can use my HP financial calculator to solve this but I was hoping to have a formula that I could use in excel. But like you, I cant see how to solve for r.10/11/18

James W.

10/08/18